Rain Measurement Simulation Using the Hall Effect Flow-Meter - Sirenden, Bernadus Herdi (Talenta Publisher, 2020)
The sensor analysis or flow-meter measuring instrument has been successfully carried out on the signal output to see the stability or accuracy of a measurement. The flowmeter measurement value was analyzed using a rainfall simulator. The rainfall intensity value will then be predicted using the Kalman filter. Kalman filters can predict various data or output signals so that the measurement results can be more stable and accurate. This research methodology consists of several stages, namely the stages of literature study, designing research tools and components, designing systems, making or assembling tools, testing all components, programs and testing the flow-meter output signal record. The flowmeter is controlled by the Arduino Nano microcontroller. Tests were carried out in this study ten times, with a time span of 60 seconds for each experiment. The increase in water flow was detected by the flow-meter which was then captured by the hercules application and the data was then copied to Ms. Excel. After the rainfall intensity value is obtained, the value will be estimated using the Kalman filter. The estimation results will show the stability and accuracy value of the flow-meter.